Primary Sjogren's Syndrome Presenting with Renal Tubular Acidosis and Central Pontine Myelinolysis: A Case Report - Sui RUBO,; Lei ZHANG2, (Archives of Rheumatology, 2013)
In this case report, we present a-75-year-old female case of primary Sjogren's syndrome (pSS) with distal renal tubular acidosis (RTA) as revealed by severe hypokalemia along with normal anion gap metabolic acidosis and abnormally acidified urine. The patient had a brain stem lesion as confirmed by quadriplegia, hypersomnia, and dysphagia. Laboratory tests revealed that the anti-Ro/SSA and anti-La/SSB antibodies were positive. Magnetic resonance imaging of the brain showed a hyperintense signal at T1 and T2 in the mid-pons, a typical characteristic of central pontine myelinolysis.